Concentration and inequalities in the financing of obras sociales after deregulation: a comparative analysis of the years 2004 and 2011 - María Florencia Arnaudo; Fernando Lago; Nebel Moscoso; Ernesto Báscolo; Natalia Yavich (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2016)
In Argentina, during the decade of the 1990s major changes were introduced into the regulatory framework of the national obras sociales, or union-based health coverage plans. Using data from the Federal Administration of Public Income (AFIP) [Administración Federal de Ingresos Públicos], this study evaluates for the years 2004 and 2011: a) the importance of obras sociales within the healthcare system, b) the degree of concentration of this health social security subsystem, and c) the inequalities in the availability of funds among the obras sociales and their beneficiaries. The results show an increased importance of obras sociales within the Argentine health system. The concentration of funds distributed to the most important institutions within the subsystem showed no change, while the concentration of contributors to these institutions slightly increased and that of beneficiaries decreased. Finally, a reduction of the inequalities in funds per beneficiary received by different institutions was observed. This trend can be explained, among other factors, by the attenuation of wage differentials between branches of economic activity and the actions of the so-called Solidarity Redistribution Fund.